Reaction Kinetics of Chlorine Corrosion to Heating Surfaces during Coal and Biomass Cofiring - Yongzheng Wang; Yu Sun; Maozhen Yue; Yungang Li (Journal of Chemistry, 2020)
The high content of chlorine in biomass will cause serious ash deposition and corrosion problems on the heating surface in boiler, reduce heat transfer efficiency, and endanger the boiler operation safety. On the basis of discussing the mechanism of chlorine corrosion to heating surface in the boiler, the temperature, atmosphere, and fouling in the boiler are simulated by high-temperature reaction device. Reaction kinetics of chlorine corrosion to heating surfaces during coal and biomass cofiring was studied by the weight gain method, which provides a theoretical basis for solving the problem of corrosion and improving the safety of boiler operation. The results show that the weight gain caused by corrosion increases with time, and its curve is in accordance with the parabola. In the early stage, the corrosion rate is very fast, and the corrosion gradually slows down after the protective layer is formed. The mixing ratio of straw biomass increases, and the corrosion rate increases proportionally. With the increase in temperature, the rate of corrosion reaction increases continuously. When the temperature exceeds 600°C, the corrosion reaction rate increases greatly. The concentration of HCl in the gas phase increases and the rate of corrosion reaction increases rapidly. Under the constant temperature, the reaction kinetics characteristics of chlorine corrosion were analyzed by model function matching. The best kinetic model function for calculating the kinetic parameters was determined, and the kinetic equation of corrosion reaction was established to quantitatively characterize the corrosion reaction.